Scratch-resistant super-hard glass polishing method
By optimizing the composite abrasive structure and polishing process, the problems of high removal rate and low scratches on ultra-hard glass surfaces have been solved, achieving efficient and environmentally friendly polishing results, suitable for glass polishing of consumer electronics products and medical devices.
Patent Information
- Application Number
- CN202511080114.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-08-04
AI Technical Summary
Existing polishing technologies struggle to achieve a synergistic optimization of high removal rates and low scratches on ultra-hard glass surfaces, and also suffer from high production costs, complex processes, and environmental pollution.
A polishing slurry was prepared using composite abrasives, consisting of 3-aminopropyltrimethoxysilane, acid anhydride compounds, cerium oxide powder, and zinc chloride aqueous solution. The polishing process was optimized by using a mixture of isohexadecane, methyl oleate, and sodium gluconate as the matrix, combined with water rinsing and ultrasonic treatment.
It achieves synergistic optimization of high polishing speed and ultra-low roughness, reduces production costs, improves production efficiency, is suitable for mass polishing, and reduces environmental impact.
Smart Images

Figure BDA0005530633640000111 
Figure BDA0005530633640000121
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of polishing, in particular to a scratch-resistant super-hard glass polishing processing method. BACKGROUND
[0002] With the rapid development of electronic consumer products (such as mobile phones, tablets, smart watches, vehicle-mounted electronic devices, etc.) and high-end medical instruments, the performance requirements of protective glass are becoming higher and higher. The protective glass of these devices not only needs to have high hardness to resist scratches in daily use, but also needs to have high smoothness to ensure optical performance and aesthetics. However, traditional polishing techniques have many problems when dealing with such super-hard glass.
[0003] Chinese patent application CN114806501A discloses a modified diamond powder, a preparation method, a use, and a polishing liquid containing the same. The use of steric hindrance modified diamond powder can improve the suspension, but the diamond has extremely high hardness and is easy to produce micro-cracks on the surface of super-hard glass. Moreover, the universality of the oily system for ceria abrasives is limited, and an additional dispersant is still needed to maintain stability for a long time.
[0004] Another Chinese patent application CN119144237A discloses a modified epoxy-cerium oxide polishing liquid and a preparation method thereof, which uses epoxy carboxylic acid to coat cerium oxide. Although the service life of the slurry is extended, the epoxy shell reduces the exposure of the chemical active centers of cerium oxide, resulting in limited improvement of the removal rate, and the scratch inhibition effect on high-hardness glass is not obvious.
[0005] In the prior art, chemical mechanical polishing (CMP) is a commonly used method for polishing glass, but it is often difficult to meet the requirements of high removal rate and low scratch when dealing with high-hardness glass. For example, although traditional cerium oxide abrasives have certain polishing effect, they are easy to produce micro-cracks and scratches on the surface of high-hardness glass, affecting the appearance and performance of the product. In addition, although some modified abrasives improve the polishing effect to some extent, they often require complex preparation processes and additional equipment modification, increasing production costs and process complexity.
[0006] In addition, existing polishing processes usually need to be carried out at high temperature or in a specific chemical environment, which not only increases energy consumption, but also may cause environmental pollution. At the same time, the parameter window of these processes is narrow, which is difficult to seamlessly connect with existing large-scale production lines, limiting their application in actual production.
[0007] Therefore, it is an urgent problem to be solved in the current technical field to develop an efficient, environmentally friendly, and low-scratch super-hard glass polishing process. SUMMARY
[0008] In order to solve the problems in the prior art, the present application provides an anti-scratch superhard glass polishing method.
[0009] In order to achieve the above-mentioned application purposes, the present application adopts the following technical solutions:
[0010] An anti-scratch superhard glass polishing method is as follows:
[0011] Step 1, the anti-scratch superhard glass after grinding is loaded into a polishing machine, and a polishing leather and a Teflon gear ring are fixed;
[0012] Step 2, isohexadecane, methyl oleate, sodium gluconate and isohexadecanol polyoxyethylene ether are used as a base, and a composite abrasive is added to prepare a polishing liquid;
[0013] Step 3, the polishing liquid is injected into the polishing machine, and polishing is performed, and water is continuously sprayed during polishing;
[0014] Step 4, after polishing, water ultrasonic treatment is performed, and the anti-scratch superhard glass is obtained.
[0015] The preparation method of the composite abrasive is as follows:
[0016] S1, 3-aminopropyltrimethoxysilane, an acid anhydride compound and cerium oxide powder are reacted in a mixed solvent containing N,N-dimethylformamide and water, and a carboxylated product is obtained after centrifugation, washing and drying;
[0017] S2, the carboxylated product of step S1 is dispersed in an aqueous zinc chloride solution, and after ultrasonic and water bath stirring, an aqueous imidazole compound solution is added for continuous reaction, and the composite abrasive is obtained after centrifugation, washing and drying.
[0018] Preferably, the anti-scratch superhard glass polishing method is as follows, in terms of weight parts:
[0019] Step 1, select the anti-scratch superhard glass after grinding, and paste the polishing leather on the rigid cast iron support disc; select the Teflon gear ring to ensure zero-backlash engagement with the inner and outer gear rings in the machine;
[0020] Step 2, mix 60-80 parts of isohexadecane, 5-15 parts of methyl oleate, 0.5-1.5 parts of sodium gluconate and 1-1.5 parts of isohexadecanol polyoxyethylene ether, stir at 600-1000 rpm for 5-10 min at 20-40℃, to obtain a polishing base liquid; add 0.2-0.6 parts of the composite abrasive to the polishing base liquid, and stir at 600-1000 rpm for 20-40 min at 20-40℃, to obtain the polishing liquid;
[0021] Step 3, adding the polishing solution prepared in step 2, the initial amount of the polishing solution added in the polishing machine covers the surface of the polishing skin to form a uniform liquid film, and the polishing solution is supplemented by 3-5% of the total weight every 20-40 min, and the polishing is continued with water spray washing;
[0022] Step 4, after the polishing is completed, the water ultrasonic treatment is used to obtain the scratch-resistant superhard glass.
[0023] The polishing skin in step 1 is at least one of a damping cloth and a polyurethane.
[0024] The polishing parameters in step 3 are polishing for 1-2 h under a pressure of 200-300 kg, an upper disc speed of 5-15 rpm, a lower disc speed of 15-25 rpm, and a sun wheel speed of 5-15 rpm.
[0025] The spray washing speed in the polishing in step 3 is 50-200 mL / min.
[0026] The ultrasonic treatment in step 4 has an ultrasonic frequency of 20-60 kHz, an ultrasonic power of 200-400 W, a water temperature of 40-60°C, and a time of 90-150 s.
[0027] The preparation method of the composite abrasive is as follows, and the proportions are by weight:
[0028] S1, 8-12 parts of 3-aminopropyltrimethoxysilane are added to 180-220 parts of N,N-dimethylformamide, 4-8 parts of an anhydride compound are added, stirring is performed at room temperature for 1-3 hours to obtain an adduct solution; 50-90 parts of cerium oxide powder are added to 160-220 parts of a mixed solvent to obtain a suspension, the mixed solvent is composed of N,N-dimethylformamide and water in a volume ratio of 2-4:1; the suspension is added to the adduct solution, continuous stirring is performed for 1-5 hours, centrifugation is performed at 3000-6000 rpm for 5-10 min, and the product is washed with water and anhydrous ethanol for 1-3 times in sequence, and drying is performed at 60-80°C for 2-8 hours to obtain a carboxylated product;
[0029] S2, 15-25 parts of the carboxylated product prepared in step S1 are added to 200-400 parts of a 0.1-0.2 mol / L zinc chloride aqueous solution, ultrasonic treatment is performed for 10-30 min, the ultrasonic power is 100-300 W, the ultrasonic frequency is 20-60 kHz, 70-80°C water bath stirring is performed for 10-30 min to uniformly disperse the particles, 400-800 parts of a 0.3-0.4 mol / L imidazole compound aqueous solution is added, stirring is continued for 10-40 min, and after stopping, cooling is performed to room temperature, centrifugation is performed at 3000-6000 rpm for 5-15 min, and the product is washed with water and anhydrous ethanol for 1-3 times in sequence, and drying is performed at 60-80°C for 5-15 hours to obtain a composite abrasive.
[0030] The acid anhydride compound is at least one of succinic anhydride, maleic anhydride, and succinic acid.
[0031] The imidazole compound is at least one of imidazole, 2-ethylimidazole, and 2-aminoimidazole.
[0032] The composite abrasive can also be composed of cerium oxide and praseodymium oxide in a mass ratio of 8-9:1.
[0033] The roles of each substance in the composite abrasive preparation method are as follows:
[0034] 3-Aminopropyltrimethoxysilane, used as a silane coupling agent, undergoes a ring-opening reaction between its amino group (-NH2) and maleic anhydride, anchoring the carboxyl group (-COOH) to the cerium oxide surface, thus facilitating subsequent Zn production. 2+ Coordination provides the site.
[0035] Maleic anhydride reacts with the amino group of silane to open the ring and generate a carboxyl group, increasing the carboxyl group density on the cerium oxide surface and enhancing its affinity for Zn. 2+ The ability to combine.
[0036] Cerium oxide powder, used as the abrasive core, provides hardness and chemical activity; its surface contains Ce. 3+ / Ce 4+ Redox activity promotes the breaking of Si-O bonds in glass.
[0037] N,N-Dimethylformamide, as a polar solvent, dissolves silane and maleic anhydride to form a homogeneous reaction system, ensuring uniform dispersion of cerium oxide.
[0038] Zinc chloride provides Zn 2+ Ions coordinate with carboxyl groups on the surface of cerium oxide to form initial complexes, promoting self-assembly to form composite abrasives.
[0039] 2-Ethylimidazole, as an organic ligand, has an imidazole ring that interacts with Zn. 2+ Coordination constructs a porous shell; the steric hindrance of the ethyl chain enhances coordination stability, and hydrophobicity optimizes the dispersion of the abrasive in oily base fluids.
[0040] Compared with existing technologies, it has the following advantages:
[0041] 1) This invention accelerates the polishing speed by optimizing the composite abrasive structure, achieving synergistic optimization of high removal rate and ultra-low roughness, and completely eliminating microcracks and scratches caused by traditional processes.
[0042] 2) The polishing method of the present invention is simple and easy to implement, highly compatible with existing production lines, and does not require large-scale modification of existing equipment, thereby reducing production costs and improving production efficiency. It is suitable for mass polishing of wearable and consumer electronics (mobile phones, watches, medical devices, vehicle electronic control panels, etc.).
[0043] 3) The raw materials and processes used in this invention are more environmentally friendly, reducing the impact on the environment and also benefiting the health and safety of operators. Detailed Implementation
[0044] Main source of materials:
[0045] Scratch-resistant ultra-hard glass, silicon 40-50%, aluminum 25-35%, zinc 7-13%, crystal phase: zinc spinel, Mohs 7-8.5, crystallinity: 30%.
[0046] Isomeric deca-ol polyoxyethylene ether, model: E-1006, Jiangsu Haian Petrochemical Plant.
[0047] Polished leather, surface material: polyurethane, Dongguan Xinaozhong Abrasive Technology Co., Ltd.
[0048] Cerium oxide powder, average particle size 40nm, model: HC-12, Guangdong Hongcai Nanomaterials Technology Co., Ltd.
[0049] Praseodymium oxide, average particle size 40nm, catalog number: NO-R-007-1, Shanghai Naio Nanotechnology Co., Ltd.
[0050] All other raw materials used in the embodiments and comparative examples of this invention are commercially available products.
[0051] Example 1
[0052] A method for polishing scratch-resistant, ultra-hard glass is as follows, in parts by weight:
[0053] Step 1: Select scratch-resistant ultra-hard glass that has been ground with 3000# abrasive, with a diameter of 44.2mm and a thickness of 2.02mm, and no chipping or cracks on the surface; attach the polishing sheet to the rigid cast iron support plate; select a φ44.6mm×1.5mm Teflon gear ring, 46 holes / sheet; tooth pitch 4.00mm±0.02mm, tooth profile angle 60°, to ensure zero backlash meshing with the inner and outer gear rings of the machine;
[0054] Step 2: Mix 70 parts of isohexadecane, 10 parts of methyl oleate, 1 part of sodium gluconate, and 1.2 parts of isodecyl alcohol polyoxyethylene ether, and stir at 800 rpm for 8 minutes at 30°C to obtain the polishing base liquid; add 0.4 parts of composite abrasive to the polishing base liquid, and stir at 800 rpm for 30 minutes at 30°C to obtain the polishing liquid.
[0055] Step 3, add the polishing solution prepared in step 2, the initial amount of the polishing solution added in the polishing machine covers the surface of the polishing skin to form a uniform liquid film, and the polishing solution is supplemented by 4% of the total weight every 30 min, and then the polishing is performed, the polishing parameters are 1.5 h of polishing under a pressure of 250 kg, 10 rpm of upper disc / 20 rpm of lower disc / 10 rpm of sun wheel; and the water rinsing is continuously performed at 100 mL / min during the polishing;
[0056] Step 4, after the polishing is completed, the water ultrasonic treatment is performed, the ultrasonic frequency is 40 kHz, the ultrasonic power is 300 W, the water temperature is 50℃, and the time is 120 s, and the anti-scratch superhard glass is obtained.
[0057] The composite abrasive is composed of cerium oxide and praseodymium oxide in a mass ratio of 8.5:1.
[0058] Example 2
[0059] The anti-scratch superhard glass polishing processing method is basically the same as that in example 1, and the only difference is that the preparation method of the composite abrasive is different.
[0060] The preparation method of the composite abrasive is as follows, in terms of weight parts:
[0061] S1, 10 parts of 3-aminopropyltrimethoxysilane are added into 200 parts of N,N-dimethylformamide, 6 parts of maleic anhydride are added, stirring is performed at room temperature for 2 hours to obtain an adduct solution; 70 parts of cerium oxide powder are added into 180 parts of a mixed solvent to obtain a suspension, the mixed solvent is composed of N,N-dimethylformamide and water in a volume ratio of 3:1; the suspension is added into the adduct solution, continuous stirring is performed for 4 hours, 4000 rpm centrifugation is performed for 8 min, and then the product is washed with water and anhydrous ethanol respectively for 1 time, and then the product is dried at 70℃ for 5 hours to obtain a carboxylated product;
[0062] S2, 20 parts of the carboxylated product prepared in step S1 are added into 300 parts of a 0.13 mol / L zinc chloride aqueous solution, ultrasonic treatment is performed for 20 min, the ultrasonic power is 200 W, the ultrasonic frequency is 40 kHz, 75℃ water bath stirring is performed for 20 min to uniformly disperse the particles, 600 parts of a 0.35 mol / L 2-ethylimidazole aqueous solution is added, and then stirring is continuously performed for 30 min, and then the product is cooled to room temperature after stopping, 4000 rpm centrifugation is performed for 10 min, and then the product is washed with water and anhydrous ethanol respectively for 1 time, and then the product is dried at 70℃ for 10 hours to obtain a composite abrasive.
[0063] Example 3
[0064] The anti-scratch superhard glass polishing processing method is basically the same as that in example 1, and the only difference is that the preparation method of the composite abrasive is different.
[0065] The preparation method of the composite abrasive is as follows:
[0066] S1, 10 parts of 3-aminopropyl trimethoxysilane was added into 200 parts of N,N-dimethylformamide, 6 parts of succinic acid was added, stirred at room temperature for 2 hours to obtain an adduct solution; 70 parts of cerium oxide powder was added into 180 parts of mixed solvent to obtain a suspension; the mixed solvent was composed of N,N-dimethylformamide and water in a volume ratio of 3:1; the suspension was added into the adduct solution, continuously stirred for 4 hours, centrifuged at 4000 rpm for 8 min, washed with water and anhydrous ethanol respectively for 1 time in turn, and dried at 70℃ for 5 hours to obtain a carboxylation product;
[0067] S2, 20 parts of the carboxylation product prepared in step S1 was added into 300 parts of 0.13 mol / L zinc chloride aqueous solution, ultrasonic treated for 20 min with an ultrasonic power of 200 W and an ultrasonic frequency of 40 kHz, stirred at 75℃ water bath for 20 min to make the particles uniformly dispersed, 600 parts of 0.35 mol / L 2-ethyl imidazole aqueous solution was added, continuously stirred for 30 min, cooled to room temperature after stopping, centrifuged at 4000 rpm for 10 min, washed with water and anhydrous ethanol respectively for 1 time in turn, and dried at 70℃ for 10 hours to obtain a composite abrasive.
[0068] Example 4
[0069] A method for polishing and processing anti-scratch superhard glass is basically the same as that in example 1, the only difference is that the preparation method of the composite abrasive is different.
[0070] The preparation method of the composite abrasive is as follows:
[0071] S1, 10 parts of 3-aminopropyl trimethoxysilane was added into 200 parts of N,N-dimethylformamide, 6 parts of succinic acid was added, stirred at room temperature for 2 hours to obtain an adduct solution; 70 parts of cerium oxide powder was added into 180 parts of mixed solvent to obtain a suspension; the mixed solvent was composed of N,N-dimethylformamide and water in a volume ratio of 3:1; the suspension was added into the adduct solution, continuously stirred for 4 hours, centrifuged at 4000 rpm for 8 min, washed with water and anhydrous ethanol respectively for 1 time in turn, and dried at 70℃ for 5 hours to obtain a carboxylation product;
[0072] S2, 20 parts of the carboxylation product prepared in step S1 was added into 300 parts of 0.13 mol / L zinc chloride aqueous solution, ultrasonic treated for 20 min with an ultrasonic power of 200 W and an ultrasonic frequency of 40 kHz, stirred at 75℃ water bath for 20 min to make the particles uniformly dispersed, 600 parts of 0.35 mol / L 2-ethyl imidazole aqueous solution was added, continuously stirred for 30 min, cooled to room temperature after stopping, centrifuged at 4000 rpm for 10 min, washed with water and anhydrous ethanol respectively for 1 time in turn, and dried at 70℃ for 10 hours to obtain a composite abrasive.
[0073] Example 5
[0074] The method for polishing anti-scratch superhard glass is basically the same as that in Example 1, and the only difference is that the preparation method of the composite abrasive is different.
[0075] The preparation method of the composite abrasive is as follows:
[0076] S1, 10 parts of 3-aminopropyltrimethoxysilane were added into 200 parts of N,N-dimethylformamide, 6 parts of maleic anhydride were added, and stirring was carried out at room temperature for 2 hours to obtain an adduct solution; 70 parts of cerium oxide powder were added into 180 parts of a mixed solvent to obtain a suspension, wherein the mixed solvent was composed of N,N-dimethylformamide and water in a volume ratio of 3:1; the suspension was added into the adduct solution, and continuous stirring was carried out for 4 hours; centrifugation was carried out at 4000 rpm for 8 min; washing was carried out with water and anhydrous ethanol respectively for 1 time in sequence; and drying was carried out at 70°C for 5 hours to obtain a carboxylated product.
[0077] S2, 20 parts of the carboxylated product prepared in step S1 were added into 300 parts of a 0.13 mol / L zinc chloride aqueous solution, ultrasonic treatment was carried out for 20 min, the ultrasonic power was 200 W, the ultrasonic frequency was 40 kHz, stirring was carried out at 75°C water bath for 20 min to make the particles uniformly dispersed, 600 parts of a 0.35 mol / L 2-aminoimidazole aqueous solution was added, and stirring was continuously carried out for 30 min; after stopping, cooling was carried out to room temperature, centrifugation was carried out at 4000 rpm for 10 min, washing was carried out with water and anhydrous ethanol respectively for 1 time in sequence, and drying was carried out at 70°C for 10 hours to obtain a composite abrasive.
[0078] Example 6
[0079] The method for polishing anti-scratch superhard glass is basically the same as that in Example 1, and the only difference is that the preparation method of the composite abrasive is different.
[0080] The preparation method of the composite abrasive is as follows:
[0081] S1, 10 parts of 3-aminopropyltrimethoxysilane were added into 200 parts of N,N-dimethylformamide, 6 parts of maleic anhydride were added, and stirring was carried out at room temperature for 2 hours to obtain an adduct solution; 70 parts of cerium oxide powder were added into 180 parts of a mixed solvent to obtain a suspension, wherein the mixed solvent was composed of N,N-dimethylformamide and water in a volume ratio of 3:1; the suspension was added into the adduct solution, and continuous stirring was carried out for 4 hours; centrifugation was carried out at 4000 rpm for 8 min; washing was carried out with water and anhydrous ethanol respectively for 1 time in sequence; and drying was carried out at 70°C for 5 hours to obtain a carboxylated product.
[0082] S2, 20 parts of the carboxylation product prepared in step S1 was added into 300 parts of 0.13 mol / L zinc chloride aqueous solution, ultrasonic treatment was carried out for 20 min, the ultrasonic power was 200 W, the ultrasonic frequency was 40 kHz, 75℃ water bath stirring was carried out for 20 min to make the particles uniformly dispersed, 600 parts of 0.35 mol / L imidazole aqueous solution was added, and stirring was continued for 30 min, and then the system was cooled to room temperature after stopping, centrifugation was carried out at 4000 rpm for 10 min, and then washing was carried out with water and anhydrous ethanol respectively for 1 time, and then drying was carried out at 70℃ for 10 hours to obtain the composite abrasive.
[0083] Comparative Example 1
[0084] The anti-scratch superhard glass polishing method is basically the same as that in Embodiment 1, and the only difference is that the preparation method of the composite abrasive is different.
[0085] The preparation method of the composite abrasive is as follows:
[0086] S1, 10 parts of 3-aminopropyltrimethoxysilane was added into 200 parts of N,N-dimethylformamide, 6 parts of glutaric anhydride was added, stirring was carried out at room temperature for 2 hours to obtain an adduct solution; 70 parts of cerium oxide powder was added into 180 parts of a mixed solvent to obtain a suspension, wherein the mixed solvent was composed of N,N-dimethylformamide and water in a volume ratio of 3:1; the suspension was added into the adduct solution, and stirring was continuously carried out for 4 hours, centrifugation was carried out at 4000 rpm for 8 min, and then washing was carried out with water and anhydrous ethanol respectively for 1 time, and then drying was carried out at 70℃ for 5 hours to obtain a carboxylation product;
[0087] S2, 20 parts of the carboxylation product prepared in step S1 was added into 300 parts of 0.13 mol / L zinc chloride aqueous solution, ultrasonic treatment was carried out for 20 min, the ultrasonic power was 200 W, the ultrasonic frequency was 40 kHz, 75℃ water bath stirring was carried out for 20 min to make the particles uniformly dispersed, 600 parts of 0.35 mol / L imidazole aqueous solution was added, and stirring was continued for 30 min, and then the system was cooled to room temperature after stopping, centrifugation was carried out at 4000 rpm for 10 min, and then washing was carried out with water and anhydrous ethanol respectively for 1 time, and then drying was carried out at 70℃ for 10 hours to obtain the composite abrasive.
[0088] Comparative Example 2
[0089] The anti-scratch superhard glass polishing method is basically the same as that in Embodiment 1, and the only difference is that the preparation method of the composite abrasive is different.
[0090] The preparation method of the composite abrasive is as follows:
[0091] S1, 10 parts of 3-aminopropyltrimethoxysilane was added into 200 parts of N,N-dimethylformamide, 6 parts of maleic anhydride was added, and stirring was carried out at room temperature for 2 hours to obtain an adduct solution; 70 parts of cerium oxide powder was added into 180 parts of mixed solvent to obtain a suspension, wherein the mixed solvent was composed of N,N-dimethylformamide and water in a volume ratio of 3:1; the suspension was added into the adduct solution, and stirring was continuously carried out for 4 hours; centrifugation was carried out at 4000 rpm for 8 min; washing was carried out with water and anhydrous ethanol respectively for 1 time in sequence; and drying was carried out at 70℃ for 5 hours to obtain a carboxylation product;
[0092] S2, 20 parts of the carboxylation product prepared in step S1 was added into 300 parts of 0.13 mol / L zinc chloride aqueous solution, ultrasonic treatment was carried out for 20 min, the ultrasonic power was 200 W, the ultrasonic frequency was 40 kHz, 75℃ water bath stirring was carried out for 20 min to make the particles uniformly dispersed, 600 parts of 0.35 mol / L 2-methylimidazole aqueous solution was added, and stirring was continuously carried out for 30 min; after stopping, cooling was carried out to room temperature, centrifugation was carried out at 4000 rpm for 10 min, washing was carried out with water and anhydrous ethanol respectively for 1 time in sequence, and drying was carried out at 70℃ for 10 hours to obtain a composite abrasive.
[0093] Comparative Example 3
[0094] The anti-scratch superhard glass polishing method is basically the same as that of Embodiment 1, and the only difference is that the preparation method of the composite abrasive is different.
[0095] The preparation method of the composite abrasive is as follows:
[0096] S1, 10 parts of 3-aminopropyltrimethoxysilane was added into 200 parts of N,N-dimethylformamide, 6 parts of maleic anhydride was added, and stirring was carried out at room temperature for 2 hours to obtain an adduct solution; 70 parts of cerium oxide powder was added into 180 parts of mixed solvent to obtain a suspension, wherein the mixed solvent was composed of N,N-dimethylformamide and water in a volume ratio of 3:1; the suspension was added into the adduct solution, and stirring was continuously carried out for 4 hours; centrifugation was carried out at 4000 rpm for 8 min; washing was carried out with water and anhydrous ethanol respectively for 1 time in sequence; and drying was carried out at 70℃ for 5 hours to obtain a carboxylation product;
[0097] S2, 20 parts of the carboxylation product prepared in step S1 was added into 300 parts of 0.13 mol / L zinc chloride aqueous solution, ultrasonic treatment was carried out for 20 min, the ultrasonic power was 200 W, the ultrasonic frequency was 40 kHz, 75℃ water bath stirring was carried out for 20 min to make the particles uniformly dispersed, 600 parts of 0.35 mol / L 2-methylimidazole aqueous solution was added, and stirring was continuously carried out for 30 min; after stopping, cooling was carried out to room temperature, centrifugation was carried out at 4000 rpm for 10 min, washing was carried out with water and anhydrous ethanol respectively for 1 time in sequence, and drying was carried out at 70℃ for 10 hours to obtain a composite abrasive.
[0098] Comparative Example 4
[0099] The anti-scratch superhard glass polishing method is basically the same as that of Embodiment 1, with the only difference being that the composite abrasive is replaced by an equal amount of cerium oxide powder.
[0100] Test Example 1
[0101] Roughness measurement:
[0102] The anti-scratch superhard glass prepared in the embodiments and comparative examples of the application was measured for roughness using an ICON atomic force microscope from Bruker, USA, with five-point testing and a point testing area of 0.1 um x 0.1 um.
[0103] The test results are shown in Table 1.
[0104] Table 1
[0105] Experimental protocol Roughness Ra (nm) Example 1 0.51 Example 2 0.24 Example 3 0.41 Example 4 0.29 Example 5 0.33 Example 6 0.37 Comparative Example 1 0.35 Comparative Example 2 0.31 Comparative Example 3 0.38 Comparative Example 4 0.58
[0106] Test Example 2
[0107] The thickness difference of the anti-scratch superhard glass prepared in the embodiments and comparative examples of the application was measured using a thickness gauge to calculate the polishing rate, and the thickness difference before and after polishing was divided by the polishing time to obtain the polishing rate. Each test was performed three times, and the average value was obtained to obtain the average polishing rate.
[0108] The test results are shown in Table 2.
[0109] Table 2
[0110]
[0111]
[0112] In the same case of using 2-ethylimidazole, maleic anhydride was selected as the carboxylating agent in Embodiment 2, which contains a rigid double bond in the molecule, and the amino group of 3-aminopropyltrimethoxysilane acts as a nucleophile to attack the five-membered ring anhydride group to form a high-density cross-linked network through amide bond condensation. Maleic anhydride can quickly form a five-membered ring intermediate with 3-aminopropyltrimethoxysilane, and further generate a higher density of carboxyl anchor points on the surface of cerium oxide. These high-density carboxyl groups not only provide more Zn 2+ coordination sites, making the composite abrasive nucleation more uniform and thinner, but also effectively prevent the agglomeration of cerium oxide powder, improving the dispersity and exposure, thereby achieving higher removal rate and lower surface roughness under the mechanical-chemical synergistic effect. However, succinic anhydride, succinic anhydride, or glutaric anhydride have lower carboxyl density due to differences in chain length or ring tension, resulting in a relatively thick and uneven composite abrasive layer, which leads to a decrease in polishing performance.
[0113] The ethyl chain of 2-ethyl imidazole provides a moderate hydrophobic-hydrophilic balance in the oil-based base fluid, which allows the abrasive to be highly dispersed and inhibited from agglomeration, not only reducing the risk of scratches caused by agglomeration, but also enhancing the wettability of the polishing fluid to the glass substrate by reducing the contact angle, expanding the effective contact area. The steric hindrance effect of the ethyl chain makes the coordination bond with the imidazole ring more stable, thereby achieving the effect of improving the removal rate and optimizing the surface quality, while the 2-methyl imidazole lacks steric hindrance, the 2-amino imidazole is too basic, or the unsubstituted imidazole has loose coordination, which is difficult to achieve this effect. 2+ The ethyl chain of 2-ethyl imidazole provides a moderate hydrophobic-hydrophilic balance in the oil-based base fluid, which allows the abrasive to be highly dispersed and inhibited from agglomeration, not only reducing the risk of scratches caused by agglomeration, but also enhancing the wettability of the polishing fluid to the glass substrate by reducing the contact angle, expanding the effective contact area. The steric hindrance effect of the ethyl chain makes the coordination bond with the imidazole ring more stable, thereby achieving the effect of improving the removal rate and optimizing the surface quality, while the 2-methyl imidazole lacks steric hindrance, the 2-amino imidazole is too basic, or the unsubstituted imidazole has loose coordination, which is difficult to achieve
Claims
1. A method of processing an anti-scratch super-hard glass polishing, characterized in that, The method is as follows: Step 1, the anti-scratch superhard glass after grinding is loaded into a polishing machine, and the polishing leather and the Teflon gear ring are fixed; Step 2, isomeric cetane, methyl oleate, sodium gluconate and isomeric decanol polyoxyethylene ether are used as a base, and a composite abrasive is added to prepare a polishing liquid; Step 3, the polishing liquid prepared in step 2 is injected into the polishing machine, and polishing is carried out, and water is continuously sprayed during polishing; Step 4, after polishing, water ultrasonic treatment is carried out, and the anti-scratch superhard glass is obtained; The preparation method of the composite abrasive is as follows: S1, 3-aminopropyltrimethoxysilane, anhydride compound and cerium oxide powder are reacted in a mixed solvent containing N,N-dimethylformamide and water, and after centrifugation, washing and drying, a carboxylated product is obtained; S2, the carboxylated product of step S1 is dispersed in an aqueous zinc chloride solution, and after ultrasonic and water bath stirring, an aqueous imidazole compound solution is added for continuous reaction, and after centrifugation, washing and drying, a composite abrasive is obtained.
2. The method of claim 1, wherein the super-hard glass polished processing method is characterized by, The method is as follows, and the weight parts are as follows: Step 1, select the anti-scratch superhard glass after grinding, and paste the polishing leather on the rigid cast iron support disc; select the Teflon gear ring to ensure zero backlash engagement with the inner and outer gear rings of the machine; Step 2, mix 60-80 parts of isomeric cetane, 5-15 parts of methyl oleate, 0.5-1.5 parts of sodium gluconate and 1-1.5 parts of isomeric decanol polyoxyethylene ether, stir at 600-1000 rpm for 5-10 min at 20-40℃, and obtain a polishing base liquid; add 0.2-0.6 parts of the composite abrasive to the polishing base liquid, and stir at 600-1000 rpm for 20-40 min at 20-40℃, and obtain a polishing liquid; Step 3, add the polishing liquid prepared in step 2, the initial amount of polishing liquid added in the polishing machine covers the surface of the polishing leather to form a uniform liquid film, and 3-5% of the total weight of the polishing liquid is supplemented every 20-40 min, and polishing is carried out; water is continuously sprayed during polishing; Step 4, after polishing, water ultrasonic treatment is carried out, and the anti-scratch superhard glass is obtained.
3. The method of claim 1, wherein the super-hard glass polishing process is characterized by, The parameters of polishing in step 3 are 1-2 h of polishing under a pressure of 200-300 kg, 5-15 rpm of upper disc / 15-25 rpm of lower disc / 5-15 rpm of sun gear.
4. The method of claim 1, wherein the super-hard glass polished processing method is characterized by, The spraying speed of the continuously sprayed water during polishing in step 3 is 50-200 mL / min.
5. The method of claim 1, wherein the super-hard glass polished processing method is characterized by, The ultrasonic frequency of the ultrasonic treatment in step 4 is 20-60 kHz, the ultrasonic power is 200-400 W, the water temperature is 40-60℃, and the time is 90-150 s.
6. The scratch-resistant, super-hard, glass polished machining method of claim 1 or 2, wherein, The preparation method of the composite abrasive is as follows, and the weight parts are as follows: S1, take 8-12 parts of 3-aminopropyl trimethoxysilane into 180-220 parts of N,N-dimethylformamide, add 4-8 parts of anhydride compound, stir at room temperature for 1-3 hours to obtain an adduct solution; take 50-90 parts of cerium oxide powder into 160-220 parts of mixed solvent, mix uniformly to obtain a suspension; the mixed solvent is N,N-dimethylformamide and water in a volume ratio of 2-4:1; add the suspension into the adduct solution, continuously stir for 1-5 hours, centrifuge at 3000-6000 rpm for 5-10 min, wash with water and anhydrous ethanol for 1-3 times respectively, dry at 60-80°C for 2-8 hours to obtain a carboxylation product; S2, take 15-25 parts of the carboxylation product prepared in step S1 into 200-400 parts of 0.1-0.2 mol / L zinc chloride aqueous solution, ultrasonic treat for 10-30 min, ultrasonic power is 100-300 W, ultrasonic frequency is 20-60 kHz, 70-80°C water bath stirring for 10-30 min to make the particles uniformly dispersed, add 400-800 parts of 0.3-0.4 mol / L imidazole compound aqueous solution, continue to stir for 10-40 min, stop and cool to room temperature, centrifuge at 3000-6000 rpm for 5-15 min, wash with water and anhydrous ethanol for 1-3 times respectively, dry at 60-80°C for 5-15 hours to obtain a composite abrasive.
7. The processing method for polishing scratch-resistant ultra-hard glass as described in claim 6, characterized in that, The anhydride compound is at least one of succinic anhydride, maleic anhydride and succinic acid.
8. The method of claim 6, wherein the super-hard glass polishing process is scratch resistant. The imidazole compound is at least one of imidazole, 2-ethylimidazole and 2-aminoimidazole.
9. An ultra-hard, scratch-resistant glass, characterized in that, Prepared by using the processing method as claimed in any one of claims 1-8.
Citation Information
Patent Citations
Modified diamond powder, preparation method, application and polishing solution containing modified diamond powder
CN114806501A
Modified epoxy-cerium oxide polishing solution and preparation method thereof
CN119144237A
Cerium oxide and ZIF-8 composite abrasive particle as well as preparation method and application thereof
CN116285891A
Polishing solution for quartz glass substrate as well as preparation method and application of polishing solution
CN118126631A
Method for synthesizing cerium oxide composite abrasive and chemical mechanical polishing solution
CN118995136A